COMMERCIAL EXCESS AS A CAUSE OF THE GLOBAL WORLD CRISIS IN THE DEPRESSIONS OF 1929 AND 2008. THE SITUATION IN SPAIN - Aranda Prieto, Javier (2020)
The crises of the years 1929 and 2008, although distant in time, coincide in that they both cast doubt on the global economic world. By analyzing the time frame of the 2008 economic crisis, the objective of this article is to understand that the origin of this global depression was caused by excess trade volume from a continuous acceleration of production. This caused accumulated excess production in warehouses of companies, and with it, induced the instability of the business network in different nations, as happened  in countries like Spain. In the social chaos caused by excess, companies opted for a series of conservative policies such as the wage cut and the massive layoffs that caused the chronic indebtedness of the domestic economy. As a conclusion, the gradual growth of the commercial offer has shaped an interconnected financial world through social inequality since the impoverishment of the local business for the benefit of the multinationals, thereby fracturing the global society, and therefore increasing the uncertainty of a very unstable globalized world.